IN VIVO ASSESSMENT OF CHARCOAL TOOTHPASTE EFFECT ON ENAMEL APPEARANCE - A NATURAL ALTERNATIVE FOR DENTAL AESTHETICS - Alexandrina Muntean; Sebastian Candrea; Ada Gabriela Delean; Andrei Ilie Condurache; Anca Munceanu; Simina Neagoe; Meroiu Alexandru; Cristina Păcurar; Irina Lupșe (Romanian Society of Oral Rehabilitation, 2024)
Teeth colour and dental aesthetic are sensitive subjects in the contemporary society with impact in everyday life. This clinical study aims to evaluate the effect of activated charcoal-based toothpaste on tooth enamel appearance, after use for tooth brushing, 2 times a day, for 4 consecutive weeks. Material and methods. Patient assessment (n=81) was carried out in the morning session at the same clinic, using good lighting conditions by 2 calibrated operators. Colour evaluation was realised using the VITA Classical Shade Guide for selected teeth in the upper and lower arch (central incisors, canines, 1st premolars), considering the teeth mainly visible by patients in smile and speech. Patients were asked to answer a short questionnaire about preferences regarding toothpaste selection, information's about whitening toothpaste and tooth brushing technique. The results reveal statistically significant differences in shade changes for maxillary teeth (centrals incisors; p=0.021, canines; p<0.001, 1st premolars; p=0.008). In the mandible, the differences were statistically significant for canines (p<0.001) and 1st premolars (p=0.001) and non-significant for central incisors (p=0.126). According to patients' responses, 18.5% of this used whitening toothpaste daily. Only 11.1% of patients asked for dentist advice regarding whitening toothpaste. Conclusions. Toothpaste with activated charcoal produce significant changes in enamel appearance, for evaluated teeth, except central mandibular incisors, element that allow us to consider this type of toothpaste as an alternative for preserving and improving dental enamel appearance. Patients involved in this study have a tendency to consider that for toothpaste selection dentist recommendation is not always necessary.